Design Simulation of Automatic Lifted Bridge System using Arduino Uno - Kurniawan, Bambang; Aryadi, Kian; Putra, Dwi; Astharini, Dwi (Universitas Al Azhar Indonesia, 2023)
The existence of bridges is needed as a means to connect interrupted paths separated by rivers, ravines, or the sea. On the one hand, the existence of bridges is sometimes an obstacle for large ships whose shipping lanes are blocked by bridges, so a bridge is needed that is able to move up to facilitate shipping to the lane. Usually, this raised bridge system is operated manually by the operator, so it is still inefficient. In this paper, we try to create a prototype design using an Arduino Uno microcontroller that displays an automatic raised bridge system. When a large ship is detected to be passing through the bridge, the system will give a warning that traffic on the bridge will be temporarily stopped with a red traffic light marked and the portal for motorists will be closed and then continued with the bridge open to ships. But if it is detected that there are still vehicles on the bridge, then the system will warn the ship to stop for a moment waiting for conditions or conditions on the bridge to become conducive, and then the bridge opens. After the ship has been detected far away from the bridge, the system and traffic on the bridge will return to normal.